Korelasi Perubahan Tekanan Darah dengan Perubahan Kadar Kolesterol Total Pasien Prolanis yang Mendapatkan Jus Lidah Buaya (Aloe vera) - Vina Yuliawati; Ade Teti Vani; Fredia Heppy (Universitas Baiturrahmah, 2021)
Introduction: One factor of hypertension is hypercholesterolemia. Efforts to lower cholesterol levels in the blood beside taking the medicine, can also with a healthy lifestyle change and diet. Diet is an effective way to lower cholesterol levels in the blood. One of the ingredients that has the benefits of anti-hypercholesterolemia is Aloe vera. Aims: Knowing the correlation between changed blood pressure and changed the Total cholesterol for Prolanis patients with cholesterol disorder that get Aloe vera juice in the Padang Air Dingin Health Center in 2018. Method: This study was conducted on the Prolanis patient in the Padang Air Dngin Helth Center conducted from July – August 2018. The type of research used was a colerative analytic analytic with cross sectional study design. The affordable population are all prolanis patient in the Padang Air Dingin Health Center with 15 samples using simple random sampling technique. Univariate data analysis presented in the form of the average, standard deviation, minimum, maximum, and bivariates analyses using the Spearman rho test, using the SPSS program. Result: Systolic blood pressure before and after consuming Aloe vera juice obtained on average 137.26 mmHg and 119.86 mmHg. Diastolic blood pressure before and after consuming Aloe vera juice was obtained on average 86.13 mmHg and 77.80 mmHg. The amount of cholesterol before and after consuming Aloe vera juice was obtained on average 264.93 and 240.36. Systolic blood pressure obtained r = 0.875 values (very strong categories), the value P = 0,000 (P < 0.05) and at the diastolic blood pressure obtained r = 0.631 values (strong categories), Value P = 0,012 (P < 0.05). Conclusion: there is a correlation betweeen changed blood pressure and changed the total cholesterol for patients with cholesterol disorder (hypercholesterolemia) that get aloe vera juice in the Padang Air Dingin Health Center in 2018.